Implementation of Social Science Learning on Character Building of Students in Elementary Schools - Nur’im Septi Lestari (Universitas Muhammadiyah Enrekang, 2022)
The school curriculum assists students in developing the knowledge, skills, attitudes, values, and morals needed to participate in community life at the local, national and global levels. This study aims to determine the implementation of Social Science learning in forming students' character in elementary schools. This research is a literature review research using the Google Scholar search engine with a total of 68 articles. The results obtained 11 articles that were by the inclusion and exclusion criteria. The results showed that the process of implementing or implementing Social Science learning was carried out properly by the goals of national education and then carried out character education or formed the character of elementary school students by the cultural character of the local community. However, there are several obstacles such as the problem of assessing attitudes and environmental factors, so the solution to overcome the problem is to make an assessment format and install monitoring cameras in every hallway and classroom.